Effect of sleep deprivation and daylight restriction on the immune response to Escherichia coli-induced septicemia in Wistar rats. Issue 1 (31st December 2023) - Ige, Abayomi O.; Agbo, Esther O.; Brown, Dorcas J.; Mebude, Olakunle O.; Adewoye, Elsie O.
ABSTRACT: Circadian rhythms influence the immune response. Its disruption can therefore alter the immune response of the host to pathogens. This study was designed to investigate the effects of two circadian disruptors, sleep-deprivation (SD) and daylight-restriction (DLR), on the immune response to septicemia which was induced using low-dose Escherichia coli (0.1 mL i.p.) (ECIS). Forty-eight Wistar rats (150–180 g) were grouped into six (n = 8): I(control), II(control+ECIS), III(SD12hrs+ECIS), IV(SD96hrs+ECIS), V(DLR12hrs+ECIS), and VI(DLR96hrs+ECIS) respectively. Following either SD or DLR in experimental groups, ECIS was induced and systemic immune response was evaluated after 7 days. Innate (leucocytes, eosinophils, IFN-γ and TNF-α) and adaptive (immunoglobulin -G and -M) immune responses was altered in short and long-term sleep deprived ECIS groups while only innate immune responses were impaired in the short-term daylight-restricted group. Spleen histology exhibited pathologies that worsened with increasing durations of SD and DLR. In conclusion, the immune response in Wistar rats to systemic infection is weakened to a greater extent by sleep-deprivation than by daylight-restriction.